Comparison of four different assays to evaluate cellular-mediated immunity against cytomegalovirus in solid organ transplantation - Casas-Parra, Angela; Veltman, Hendrik; Romero-Caballero, Alba; Gelpi-Remiro, Rosana; Boigues-Pons, Marc; Allalou, Imán; Linares-Pardo, Ian; Vila-Santandreu, Anna; Martínez-Cáceres, Eva; Iglesias-Escudero, María (Frontiers in Immunology, 2025)
CMV infection is the most prevalent opportunistic infection following solid organ transplantation (SOT), significantly affecting both graft and patient survival. Effective control of viral replication is crucial to prevent CMV infection from progressing to end-organ disease. Despite its high prevalence, options for preventing CMV infection and end-organ disease are limited to a few antiviral drugs, which have severe side effects and may lead to resistance. In this context, measuring CMV-specific cell-mediated immunity (CMI) has proven to be a valuable tool, with high negative predictive value (NPV) for the absence of CMV viremia in patients with positive tests. This study aimed to evaluate the sensitivity and specificity of various cellular immune response assays and assess the feasibility of incorporating them into routine clinical practice for kidney transplant recipients (KTR). Conducted at the Hospital Universitari Germans Trias i Pujol (HGTP), the study analyzed 56 samples from KTR and 10 healthy controls (HC). Patients and controls were classified based on their pre-transplant serostatus, and CMI was measured using QuantiFERON-CMV® ELISA, T cell proliferation assay (TCPA), activation-induced marker (AIM) assay, and an in-house ELISA. The AIM assay demonstrated that CD69 is a reliable activation marker for flow cytometry-based assays, as it consistently increased following polyclonal stimulation. Notably, among the total patient cohort with CD4 T cell reactivity, the CM subpopulation exhibited the most significant increase (p < 0.001). Comparative analysis revealed that both ELISAs had high sensitivity and specificity compared to other techniques. The consistency test results showed perfect and almost perfect agreement between the AIM (cut-off 0.2) and the QuantiFERON-CMV® ELISA and in-house ELISA, respectively. The study also explored the feasibility of incorporating these tests into daily clinical practice, proposing an algorithm based on test results and cost-effectiveness. This algorithm involves testing patients using the QuantiFERON-CMV® assay, followed by AIM testing in cases of indeterminate results or HLA mismatches. Incorporating these assays would help identify patients at the lowest risk of CMV infection after prophylaxis, enabling more selective and personalized prophylactic strategies.